Lessons learned on research uptake by next users - Blundo Canto, Genowefa M. (International Center for Tropical Agriculture, 2016)
CIAT is the leader of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), and much of CIAT’s work contributes directly to this global effort. The strength of CIAT’s climate change research is its focus on disseminating solid research results through partnerships. In order to understand the key elements of success of this participatory and user-oriented approach, CIAT is implementing a simple but effective monitoring and evaluation (M&E) system. This includes monitoring results and conducting external validation studies. Based on this M&E system, 3 main lessons have been learned during the past year and a half, which are relevant to policy makers and investors.